Field report contributed by Dick Bierman, fall 1982 - Bierman, Dicket al (1982)
Field report contributed by Dick Bierman. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1982. Epson - sheet feed